Comparative Study on Currency Recognition System Using Image Processing (International Journal of Engineering and Computer Science, 2014)
In the world, currency is the main role as medium of exchange where government of many countries introduces as banknotes and coins that is. Indian rupees, dollar, Yuan, dinar etc. in different appearance such as picture of our leaders, different color, size, serial numbers, watermarks. At same time people handled difficult to recognize currencies from different countries. The purpose of the paper is to help people solve these difficulties by comparing with another methodology. However, currency recognition system that are based on image analysis entirely are not sufficient. Our system is based on image processing and makes the process easy and user friendly to recognize all kind of banknotes. In this paper we have use Indian currency i.e. Rupees